Improving Puskesmas Staff Competency Through Office Application Workshop At Puskesmas Selindung - Wishnu Probonegoro; Lili Indah Sari; Sujono; Ellya Helmud (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2021)
Puskesmas is a health service facility that organizes public health efforts and first-level individual health efforts, service agencies that provide services to the community, really need the speed of information services so that they can provide optimal services to the community. To provide optimal and maximum service to the community, the puskesmas needs to increase the competence of the staff at the puskesmas by conducting office application workshops for their staff. For the puskesmas staff in Selindung, there are already some who know how to use office applications such as word, excel and powerpoint. But in detail in the use and utilization of office applications in more detail, they still do not understand and are not optimal. This is what makes the author and the team collaborate with the Puskesmas Selindung to carry out a work shop for office applications for puskesmas staff. The purpose of this workshop is to increase the competence of Pusekesma staff in the use and use of computers, especially in office applications, including Microsoft Word, Microsoft Excel and Microsoft PowerPoint. Because these three applications are often used for data and information needs managed by the Selindung health center. The method used in this activity is a workshop and training model. That is by conducting lectures or giving material, and directly practised